DAMPAK DIGITALISASI TERHADAP INKLUSI KEUANGAN DI BANK SYARIAH INDONESIA (BSI) KOTA SAMARINDA - Jannah, Miftahul; Kamsiah, Kamsiah; Santoso, Agus (At-Tawazun, Jurnal Ekonomi Syariah, 2025)
Digitalization in the financial sector has brought significant changes in the way financial services are delivered and accessed, including in Islamic financial institutions such as Bank Syariah Indonesia (BSI). Digital technology has great potential to increase financial inclusion by providing faster, cheaper, and more accessible services, of course, which must be in accordance with sharia principles. The adoption of technologies such as mobile banking, internet banking, and e-wallets allows customers to access services anytime and anywhere. This study uses a mixed method with a quantitative survey approach and in-depth descriptive analysis and will be carried out in Samarinda City in 2024 with data from BSI in Samarinda in 2023. The results of this study show that BSI's digital services in Samarinda City have been widely adopted, with the highest adoption in ATM (100%) and Mobile Banking (90%) services due to ease of access, transaction speed, and good security.